PELATIHAN PEMANFAATAN SAMPAH DAPUR MENJADI ANEKA MENU MAKANAN YANG LAYAK KONSUMSI, LEZAT, DAN SEHAT BAGI ANGGOTA PKK RW 13 RT 08 KELURAHAN BARENG KECAMATAN KLOJEN KOTA MALANG - Shinta Maharani Trivena; Kartika Indah Permanasari; Nilawati Fiernaningsih; Kun Mustain; Zubaidi Zubaidi (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2018)
Community service aims to reduce the amount of kitchen waste because it will be processed as food. Items that are useless and underestimated and disposed of are processed into menus that are suitable for consumption, healthy, and delicious. Besides that, it can also be used as an opportunity for entrepreneurship. The implementation method is in the form of cooking training. The food produced is siomay which is made from the basic ingredients of the head of shrimp and broccoli stems, martabak which is given a mixture of vegetable stems and onion skin, and knows meatballs made from the head of shrimp and broccoli stems. The object in this PKM activity was a member of PKK RT 13 RW 08 Bareng, Klojen Subdistrict, Malang City. The output that will be produced in this PKM activity is in the form of food products. This PKM activity is held on Jl. Bareng Raya street 2n / 538 Bareng, Klojen Sub District, Malang City